The Role of Mannose-Binding Lectin and Inflammatory Markers in Establishing the Course and Prognosis of Community-Acquired Pneumonia in Children - Roxana Taraș; Beatrice Mahler; Mihaela Bălgrădean; Diana Derewicz; Miruna Ioana Lazăr; Ruxandra Vidlescu; Florian Berghea (MDPI AG, 2023)
Background: Community-acquired pneumonia (CAP) is one of the most significant childhood diseases worldwide and a leading infectious cause of death in children. This study aimed to evaluate the prognostic value of the inflammatory markers-C-reactive protein (CRP) and procalcitonin (PCT)-and the polymorphic glycoprotein mannose-binding lectin (MBL), deficiency of which is associated with severe infections, in the determination of the optimal type and timing of therapeutic intervention for CAP in childhood. Methods: Retrospective evaluation was conducted on a cohort of 204 children aged 4 months-17 years hospitalized with CAP. Their levels of CRP, PCT, and MBL were assessed for their association with a variety of outcomes, including the incidence of local and systemic complications, admission to the ICU, duration of antibiotic treatment and hospital stay, and death. Results: CRP and PCT proved to be better predictors of complications of CAP than MBL. The area under the curve (AUC) value was highest for PCT as a predictor of systemic complications (AUC = 0.931, 95%CI 0.895-0.967), while CRP (AUC = 0.674, 95%CI 0.586-0.761) performed best as a predictor of local complications (AUC = 0.674, 95%CI 0.586-0.761). Regarding admission to the ICU, CRP was the weakest predictor (AUC = 0.741), while PCT performed the best (AUC = 0.833), followed by MBL (AUC = 0.797). Sensitivity and specificity were calculated for the optimal threshold generated by receiver operating characteristic (ROC) curves, rendering sensitivity of 90% and specificity of 87% for PCT in assessing the risk of systemic complications, compared to sensitivity of 83% and specificity of 90% for CRP. MBL showed relatively high sensitivity (96%) but low specificity (25%) for predicting the need for ICU admission. Conclusions: Early measurement of CRP, PCT, and MBL provides clinicians with important information regarding the course and prognosis of children diagnosed with CAP, thus ensuring prompt, optimal therapeutic management.